Laparoscopic Ventral Mesh Rectopexy in Patients with Full Thickness Rectal Prolapse: Our Experience - Ramazan Saygin Kerimoglu (Genel Tıp Dergisi)
Objective: The gold standard method for the treatment of rectal prolapse is still unclear. This study aims to share the results of patients who underwent laparoscopic ventral mesh rectopexy surgery for rectal prolapse. Design: Only cases who underwent laparoscopic procedure were included in the study. Subjects/Patients: A total of 22 patients who were operated for rectal prolapse were analyzed. Methods: The patient’s data were evaluated including preoperative data, postoperative course and recurrence. Results: Complications were observed in 6 patients in the early postoperative period (p=0.077). Complications observed in two patients, which resolved spontaneously during follow-up with minimal bleeding and postoperative ileus. Mean follow-up time was 16 months. There was no recurrence or mortality during this period. Conclusion: Laparoscopic ventral mesh rectopexy still maintains its importance as one of the most effective options in the treatment of rectal prolapse, due to its high success rates, rapid and permanent resolution of clinical symptoms, and the positive effects of laparoscopy on quality of life.